THE REALIZATION OF THEMATIC PROGRESSION IN ONLINE IELTS WRITING TASK 2 SAMPLES IN AN ENGLISH-LEARNING WEBSITE: A CASE STUDY - Thang, Nguyen Van; Tam, Nguyen Thi Minh (VNU Journal of Foreign Studies, 2020)
This research aims at investigating the realization of thematic progression (TP) patterns, which is defined as “the way in which the theme of a clause may pick up, or repeat a meaning from a preceding theme or rheme” (Paltrigde, 2006, p. 148), and their effects on text quality of online IELTS Writing Task 2 samples. Investigated in the light of systemic functional approach, TP is classified into five patterns, namely Simple Linear Progression (SLP), Constant Progression (CP), Split Rheme Progression (SRP), Split Theme Progression (STP) and Derived Hypertheme Progression (DHP) (McCabe, 1999). In this study, the corpus consisting of 24 sample essays derived from an English-learning website was analyzed using both quantitative and qualitative methods. The results of this study highlight that SLP is the most frequently employed pattern in the corpus, followed by CP, SRP, STP and DHP patterns respectively. The analysis also shows that proper employment of TP overall is a contributing factor to the coherence and cohesion of the text, with each pattern exerting different effects. SLP, with its cross-referential links, yields a constantly developing and cohesive text whilst CP keeps a strong thematic focus. Meanwhile, SRP and STP patterns are both found to offer a planned text development and DHP creates cohesion with hypernym-hyponym relation. Problems related to the lack of TP, inappropriate theme positioning and the overuse of the theme “It” and “There” are also reported in the corpus.